Ethyl Lactate Ameliorates Hepatic Steatosis and Acute‐on‐Chronic Liver Injury in Alcohol‐Associated Liver Disease by Inducing Fibroblast Growth Factor 21 - Yang Jiang; Shuang Wei; Shiming Shen; Yuxiao Liu; Weitong Su; Dong Ding; Zengpeng Zheng; Haokai Yu; Tingting Zhang; Qiuli Yang; Jiuxiang Zhao; Yi Shen; et al. (Advanced Science)
Abstract Aberrant upregulation of hepatic lipogenesis induced by chronic and excessive alcohol consumption is a critical driver of the progression of alcohol‐associated liver disease (ALD), however, no effective approaches inhibiting lipogenesis are currently available for treating ALD patients. Moreover, little is known about whether and how nonethanol ingredients in alcoholic beverages regulate the pathogenesis of ALD. Here the discovery of a small molecule that activates the production and secretion of fibroblast growth factor 21 (FGF21) is reported. It is shown that the activator ethyl lactate, a nonethanol ingredient found in distilled liquors, ameliorates alcoholic hepatosteatosis, inflammation and acute‐on‐chronic liver injury by stimulating FGF21. In response to chronic‐plus‐binge ethanol feeding or fasting, ethyl lactate mimics lipogenesis lowering effects by stimulating FGF21 production through the NAD+‐dependent deacetylase sirtuin 1 (SIRT1) signaling pathway. These ethyl lactate‐mediated beneficial effects are abolished by inhibition of SIRT1 through injection of EX527. Importantly, FGF21 deficiency in hepatocytes blocks the downregulation of lipogenesis by ethyl lactate and exacerbates alcoholic steatosis, inflammation and liver injury. The regulatory mechanism is discussed during the pathophysiological conditions and suggests new lines of research into the therapeutic use of a foodborne small molecule ethyl lactate.